Peningkatan Kepuasan Pelanggan Melalui Keunggulan Layanan Di Industri Perhotelan Berbasis Analisis Swot (Studi Kasus: Hotel Saka Medan) - Rosari, Dina (Politeknik Pariwisata Medan, 2025)
This study aims to determine how service excellence can improve customer satisfaction at Hotel Saka Medan using a SWOT analysis tool. In the hospitality industry, service quality is a major determinant of business success in attracting and retaining customers. This study uses a qualitative approach with a case study method and data collection techniques through interviews, observation, and documentation. The results show that Hotel Saka Medan has several key strengths in the service aspect, but also faces several external challenges and internal weaknesses that need to be addressed. Recommended strategies based on SWOT are directed at maintaining strengths, overcoming weaknesses, capitalizing on opportunities, and anticipating threats.